Pokdarwis of Nagari Seribu Ngalau Efforts to Increase Fun-Tubing Tourism Development - Sari, Deswita; Susanti, Reni (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
The main issue in this research is the efforts of the Nagari Seribu Ngalau Tourism Awareness Group (Pokdarwis) in developing Fun Tubing tourism and the supporting and inhibiting factors in developing Fun Tubing tourism in Nagari Sisawah. The type of research used by the researcher is Field Research with a qualitative method and a descriptive analysis approach. Data collection techniques employed by the researcher include observation, interviews, and documentation. Data management is conducted through descriptive analysis and then explained based on the issues encountered in the field. The data sources for this research are the Head of Nagari Sisawah, the Core Management of Pokdarwis Nagari Seribu Ngalau, members of Pokdarwis Nagari Seribu Ngalau, and the community around the Fun Tubing tourism in Nagari Sisawah. To ensure the validity of the data, the researcher used source triangulation. The results of the research conducted at Pokdarwis Nagari Seribu Ngalau in their efforts to develop Fun Tubing tourism in Nagari Sisawah revealed several initiatives, such as providing facilities and infrastructure, including establishing a post, forming Pokdarwis Nagari Seribu Ngalau, and providing equipment like inflatable tubes, helmets, and life jackets, promoting through social media and word of mouth, participating in the Anugerah Desa Wisata Indonesia nomination, and organizing an annual event. The supporting factors in developing Fun Tubing tourism in Nagari Sisawah include good potential and attraction, the availability of alternative road access, services and support from the community, and improving the local economy. The hindering factors in developing Fun Tubing tourism in Nagari Sisawah are the lack of facilities, the presence of gold mining, and frequent rainy weather.